Interdisciplinary Approaches in Legal Studies: Combining Social Science and Data Science - Sagena, Unggul; Idris, Haziq; Fariq, Aiman; Khan, Omar; Sunarno, Sunarno (Rechtsnormen: Journal of Law, 2024)
Background. The integration of interdisciplinary approaches in legal studies is increasingly recognized as essential for addressing complex societal issues. Combining social science and data science offers innovative ways to analyze legal phenomena, providing deeper insights and more robust solutions. Purpose. This study aims to explore the benefits and challenges of integrating social science and data science in legal studies. The research seeks to identify effective interdisciplinary methodologies, evaluate their impact on legal research outcomes, and propose frameworks for their implementation in legal academia and practice. Method. A mixed-methods research design was employed, utilizing both qualitative and quantitative approaches. The study involved a literature review, case studies, and expert interviews to gather insights into existing interdisciplinary practices. Additionally, data analysis techniques from social and data sciences were applied to legal datasets to demonstrate the potential of these methods in enhancing legal research. Results. The findings indicate that integrating social science and data science in legal studies significantly enhances the analytical depth and breadth of legal research. Case studies revealed successful applications of interdisciplinary methods in areas such as criminal justice, human rights, and regulatory compliance. Conclusion. The study concludes that interdisciplinary approaches combining social science and data science hold great promise for advancing legal studies. Implementing these methodologies can lead to more informed legal analyses, better policy recommendations, and enhanced legal education.